Effects of experimental anaemia on intra‐erythrocytic phosphate levels in rainbow trout, Oncorhynchus mykiss - Val, Adalberto Luis; Mazur, Carl Nelson; Salvo-Souza, Roberto H. de; Iwama, George K. (Journal of Fish Biology, 1994)
The concentrations of intra‐erythrocytic adenylates (ATP, ADP and AMP) and guanylates (GTP, GDP and GMP) were determined in rainbow trout subjected to 10% blood removal every 12 h for 96 h. Haemoglobin concentration, [Hb], decreased from 6·043±0·617 to 0·957 ± 0·195 g dl−1. This decrease in [Hb] was followed by a continuous increase in total organic phosphates, e.g. adenylates plus guanylates. Intra‐erythrocytic NTP (ATP plus GTP) levels increased significantly after 48 h when haemoglobin concentration was 2·427 ± 0·256 g dl−1. Although a significant increase in GDP levels in animals with [Hb] less than 1·677 ± 0·235 g dl−1 was observed, the general increase in guanylate level was mainly due to the GMP which increased about 85‐fold during the experimental period. It is suggested that the erythrocytes of anaemic rainbow trout have the capacity to increase NTP/Hb4 ratios which may represent an advantage for anaemic fish. Copyright © 1994, Wiley Blackwell. All rights reserved